Cyber-Ethics in Multicultural Islamic Education: A Framework for Gen Z - Yusuf, Achmad; Jamhuri, M. (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study explores the integration of cyber-ethics within multicultural Islamic education frameworks specifically designed for Generation Z students. The research aims to develop a comprehensive framework that addresses the ethical challenges posed by digital technology while preserving Islamic values and multicultural perspectives. Method: A qualitative research approach was employed, utilizing semi-structured interviews with 150 participants including students, teachers, and administrators from five educational institutions in East Java, Indonesia: SMK Darut Taqwa Sengonagung, SMA Darut Taqwa Sengonagung, SMKN 1 Purwosari, SMKN Tutur, and SMA Negeri Purwosari located in Pasuruan. Data collection was conducted through focus group discussions, classroom observations, and document analysis over a six-month period from January to June 2025. Findings: The study reveals that 78.3% of Generation Z students experience moderate to severe ethical conflicts in digital environments, with 65.2% reporting difficulties in applying Islamic principles to online behavior. Statistical analysis revealed significant correlations between multicultural exposure and cyber-ethical competence (r = 0.742, p < 0.01). The research introduces the novel